2013
DOI: 10.3109/02699052.2013.801513
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for depression following mild traumatic brain injury in adults: A meta-analysis

Abstract: Primary Objective: Development of depression after TBI is linked to poorer outcomes. The aim of this manuscript is to review evidence for the effectiveness of current treatments.Research Design: Two meta-analyses were undertaken to examine the effectiveness of both pharmacological and non-pharmacological interventions for depression after mild -TBI Method and Procedures: PubMed, Medline, PsychInfo, Web of Science, and Digital Dissertations were searched and 13 studies located. Meta Analyst Beta 3.13 was used t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 45 publications
0
41
0
Order By: Relevance
“…There remains a lack of evidence on the use of pharmacological and nonpharmacological treatments after mTBI, although early information and advice has been found to have beneficial effects on recovery. 35,36 Overall, this study has highlighted that, although some people recover well after TBI, nearly half continue to experience significant persistent symptoms 1 year after mTBI. The impact of these symptoms on people's ability to function in everyday life suggests that early intervention is needed and can improve longer-term outcomes to facilitate the resolution of symptoms.…”
Section: Implications For Practicementioning
confidence: 83%
“…There remains a lack of evidence on the use of pharmacological and nonpharmacological treatments after mTBI, although early information and advice has been found to have beneficial effects on recovery. 35,36 Overall, this study has highlighted that, although some people recover well after TBI, nearly half continue to experience significant persistent symptoms 1 year after mTBI. The impact of these symptoms on people's ability to function in everyday life suggests that early intervention is needed and can improve longer-term outcomes to facilitate the resolution of symptoms.…”
Section: Implications For Practicementioning
confidence: 83%
“…[23][24][25] Clearly, more research is needed to examine the efficacy and potential mediators of 54 FANN ET AL.…”
Section: Resultsmentioning
confidence: 99%
“…Recent reviews of depression treatment literature in people with TBI conclude that serotonergic antidepressants and cognitive behavioral therapy (CBT) appear to be the most promising approaches to treating depression following TBI; however, there is an absence of high quality depression treatment trials and no published psychotherapy trials for MDD. [23][24][25] Important theoretical and preliminary work has described how CBT could be adapted for people with TBI. [26][27][28][29] Structural equation modeling has shown that post-TBI depression is consistent with cognitive behavioral theory, 30 and preliminary CBT trials have been promising for decreasing depressive symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Depression is the most commonly reported psychiatric consequence, with studies suggesting that up to 28.6% of TBI patients develop major depression within 1 year following injury [34][35][36]. However, the present treatment of post-TBI depression is far from satisfactory [37]. Hence studying its treatment is clearly essential.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, unfavorable outcomes in clinical trials have limited their clinical application. A recent meta-analysis showing the overall effect of anti-depression drugs used in post-TBI depression suggests that active treatment is no more beneficial than placebo [37]. Methylphenidate was the only drug superior to placebo [57].…”
Section: Discussionmentioning
confidence: 99%